(untitled) (LACCEI, 2024)
In the present investigation, pastes from recycled concrete powder (RCP) with a particle size of 75 µm (200 mesh) were alkaline activated at different concentrations of alkaline solution (AS) in the order of 4M, 6M, 8M and 10M NaOH, which were compared with a paste made with ordinary Portland cement (OPC). For the preparation of the specimens, a ratio of SA/ PCR = 0.18 was used, which were cured at room temperature for 24 hours, then the curing was continued in an oven at 40°C for 72 hours and later the curing was completed up to 7 days at room temperature. The PCR was obtained from the pulverized concrete specimens tested at the Composite Materials Laboratory of the School of Materials Engineering - UNT. With respect to the compressive strength (CR) tests, values of 10.26 MPa, 10.75 MPa, 13.66 MPa, 25.53 MPa and 30. 10 MPa for the 4M, 6M, 8M and 10M concentrations of NaOH respectively, which represents increases of 5%, 33%, 149% and 193% with respect to the value of the CPO pastes, for the bulk density values the tendency was to increase with the increase of the NaOH concentration, being the highest value of 2123 kg/m3, for the specimen elaborated with a 10 M NaOH SA, which represents an increase of 24% with respect to the value of the CPO pastes. All the samples were evaluated by stereoscopy, from these observations it is concluded that the increase of the NaOH concentration decreases the apparent porosity of the pastes the pastes after being tested by compression were pulverized and characterized by FTIR, the spectra allowed to determine that, in the range of wave number from 700 to 1500 cm-1 Si-O stretching from the SiO4 tetrahedra is observed, at 870 cm-1 the vibrations of -CO3 becoming CaCO3 are observed, at 930 cm-1 the formation of hydrated calcium silicate gels (CSH) is observed, and above 3645 cm-1 the O-H stretching vibration of portlandite is observed.